2009
DOI: 10.1158/0008-5472.can-09-0043
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1 + EGF-Initiated Invasive Potential in Transformed Human Keratinocytes Is Coupled to a Plasmin/MMP-10/MMP-1–Dependent Collagen Remodeling Axis: Role for PAI-1

Abstract: The phenotypic switching called epithelial-to-mesenchymal transition is frequently associated with epithelial tumor cell progression from a comparatively benign to an aggressive, invasive malignancy. Coincident with the emergence of such cellular plasticity is an altered response to transforming growth factor-B (TGF-B) as well as epidermal growth factor (EGF) receptor amplification. TGF-B in the tumor microenvironment promotes invasive traits largely through reprogramming gene expression, which paradoxically s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
81
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(84 citation statements)
references
References 46 publications
1
81
0
Order By: Relevance
“…2,6,[13][14][15] PAI-1 is induced in migratory cells regardless of lineage, as well as in epithelial cells undergoing epithelial-to-mesenchymal (EMT)-like transitions upon expression of the E-cadherin transcriptional repressors Snail, Slug, or E47. 16,17 Keratinocytes and other epithelia undergo at least a partial EMT following wounding or directional migration [18][19][20] with up-regulation of uPA, the uPA cell surface receptor (uPAR), and PAI-1 at the migratory front. 6 Motile cells focalize both uPA (via interaction with uPAR) and PAI-1 (upon binding to uPA/ uPAR) to the leading edge, where they function in the interrelated events of matrix restructuring and migration.…”
Section: Discussionmentioning
confidence: 99%
“…2,6,[13][14][15] PAI-1 is induced in migratory cells regardless of lineage, as well as in epithelial cells undergoing epithelial-to-mesenchymal (EMT)-like transitions upon expression of the E-cadherin transcriptional repressors Snail, Slug, or E47. 16,17 Keratinocytes and other epithelia undergo at least a partial EMT following wounding or directional migration [18][19][20] with up-regulation of uPA, the uPA cell surface receptor (uPAR), and PAI-1 at the migratory front. 6 Motile cells focalize both uPA (via interaction with uPAR) and PAI-1 (upon binding to uPA/ uPAR) to the leading edge, where they function in the interrelated events of matrix restructuring and migration.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer is a pathology wherein a contribution of the three stromelysins has been described quite extensively, even though with divergent molecular mechanisms (Gill et al, 2004;McCawley et al, 2004;Wilkins-Port et al, 2009). Other pathologies, for which a contribution from at least of one member of this family has been reported, mainly include cardiovascular, degenerative and auto-immune diseases.…”
Section: Stromelysinsmentioning
confidence: 99%
“…MMP-10 up-regulation in early phases of skin tumor growth is stimulated by TGF-b and EGF: the resulting high collagenolytic activity correlates with invasiveness (Wilkins-Port et al, 2009). Increased levels of MMP-10 have been also found in lung cancer (Frederick et al, 2008).…”
Section: Biological Aspectsmentioning
confidence: 99%
“…In addition, Kumawat et al (36) reported that TGF-b1 induced the expression of Wnt-5a, but not Wnt-5b, in airway smooth muscle cells. There are also a few reports that demonstrate the upregulation of MMP-10 expression during TGF-b1-induced EMT (43,44). TGF-b1 plus EGF stimulation induces expression of MMP-10 and MMP-1 in HaCaT II-4 keratinocytes and promotes the invasion ability of cells growing on collagen type I gels (43), presumably through enhanced collagen degradation.…”
Section: Discussionmentioning
confidence: 99%
“…There are also a few reports that demonstrate the upregulation of MMP-10 expression during TGF-b1-induced EMT (43,44). TGF-b1 plus EGF stimulation induces expression of MMP-10 and MMP-1 in HaCaT II-4 keratinocytes and promotes the invasion ability of cells growing on collagen type I gels (43), presumably through enhanced collagen degradation. Another report showed that the expression of MMP-10 is upregulated by TGF-b through myocyte enhancer factor 2A in mouse and human mammary epithelial cells (NMuMG and MCF10A, respectively) (44).…”
Section: Discussionmentioning
confidence: 99%